Implementasi Projek Penguatan Profil Pelajar Pancasila dalam Kurikulum Merdeka pada Sekolah Dasar - Endang Ayu Kumalasari; Sekar Dwi Ardianti; Wawan Shokib Rondli (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
P5 is a learning activity designed to develop the character and competencies of students. The project is carried out collaboratively so as to open up space for the development of self-potential. This study focuses on the implementation of the Pancasila Student Profile Strengthening Project (P5) in the Independent Curriculum in grade III at SD N 2 Bulung Kulon which aims to understand how the implementation of P5 is implemented and the supporting and inhibiting factors. This type of research is qualitative research with a case study approach. Data collection techniques are observation, interviews, and documentation. The analysis technique uses the theory of Miles and Huberman in the form of data collection, data reduction, data presentation, and verification. The results of the study show that the independent curriculum at SD N 2 Bulung Kulon has been implemented progressively with simpler and more flexible time allocation. The implementation of the independent curriculum and P5 is designed as a strategic effort to shape the nation's next generation through a flexible, contextual, and student-centered learning approach. This curriculum provides space for students to explore their potential, think critically, and collaborate in solving problems.